Traditional Health Care Practices Among Raji Tribe of Uttarakhand - Sahani, Dr. Ashok Kumar (International Journal of Aquatic Research and Environmental Studies, 2026)
The Raji tribe is one of the five tribes of Uttarakhand. Among all the tribes of Uttarakhand, Raji Tribe is the most under developed and the smallest tribe of Uttarakhand. Their population is distributed in two districts of Uttrakhand namely Pithoragarh and Champavat. Historically, they have been considered as one of the oldest communities in the region, with roots that trace back centuries. They have been called names such as Banraji, Banravat, Ban-Manush, and cave dwellers, reflecting their connection with nature and the forests where they have traditionally lived. As they have a long history of living in caves and being forest dwellers, The Raji tribe is well acquainted with plants. Due to their direct contact with nature, they have a vast knowledge of forest resources and various plant species hence they make full use of all of the forest resources and plant in the form of medicines and food. Different type of plant species are used for different types of health concerns. People of Raji tribe have their own ways of curing different kinds of disease. This study is an attempt to understand and document the traditional use of different plant and forest species as medicine in order to conserve the indigenous medicinal knowledge of Raji Tribe.